Special Economic Zones: Is it an Elixir for economic growth in South Africa - Chauke, Richard (Technium Social Sciences Journal, 2022)
With the introduction of democracy in 1994, South Africa was faced with significant issues that necessitated action to improve the levels of domestic and foreign direct investments required to accelerate economic growth. Moreover, the South African economy comprised a narrow range of exports and an over-dependence on primary production. These challenges hindered the growth within the country as well as the continent. The emergence of Special economic zones (SEZs) internationally as a policy to support industrial development targeted at incentivising economic and infrastructure development based on specific geographical areas and responding to the needs of a particular local area. This is especially useful when the government wants to extend incentives for particular activities outside designated zones. This paper is conceptual and seeks to make a critical analysis of the contribution of SEZ to the country’s economy through the use of a literature review. The article further points out the extent to which jobs, foreign direct investments, and employment were triggered by SEZ use.